TEACHER’S COMMUNICATIVE TEACHING TO ENCOURAGE STUDENTS’ CRITICAL THINKING - Rajasa, Gilang; Sari, Nadia Tiara Antik (Research And Innovation In Language Learning (RILL), 2019)
Generally, students are intended to be better in four skills matter as well as their critical thinking along learning process in the classroom. Indonesia elementary school curriculum tends to give no option to build deeper prospect of English subject for about 2x35 minutes a week. The study conducted qualitative research method. The data were obtained from two meetings classroom video recording and observation to expose other findings. The sample data were taken from the fourth grade of elementary school students. Next, interviewing the teacher to dig information from the teacher about particular activities and to get teacher’s feedback from the video that has been recorded before. Finally, distributing a questionnaire to the students to gain information from another perspective. The findings showed the teacher is not the only one factor which develops and enhance students’ critical thinking, but the students also contribute to encouraging each other to do the task. They helped other students to speak up and state their mind when the teacher tried to open discussion with the class. Besides, the teacher gave higher and lower order thinking skill to develop, express, and create students’ mindset to think and to be active along in the classroom.